2018
DOI: 10.1002/cam4.1417
|View full text |Cite
|
Sign up to set email alerts
|

Differences in clinicopathological characteristics and computed tomography findings between signet ring cell carcinoma and nonsignet ring cell carcinoma in early and advanced gastric cancer

Abstract: Signet ring cell carcinoma (SRC) of the stomach is a histological type based on microscopic characteristics. SRC's clinicopathological characteristics and prognosis are still controversial. Our study is to describe the clinicopathological features and multidetector computed tomography (MDCT) findings of patients with SRC of the stomach in comparison with nonsignet ring cell adenocarcinoma (NSRC). We retrospectively analyzed data from 241 patients who had undergone curative gastrectomy, including 62 SRC and 179… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Gastric cancer is a common malignant tumor that originates in the gastric mucosal epithelium [1]. Gastric cancer can be further classified according to the disease site, which includes gastric cardia cancer, gastric cancer, and gastric antrum cancer [2]. Recent epidemiological data have indicated that there are about 951,000 new cases of gastric cancer around the world and about 723,000 deaths due to gastric cancer, thereby ranking gastric cancer as the fifth most common and third most malignant tumor with the highest mortality rate [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric cancer is a common malignant tumor that originates in the gastric mucosal epithelium [1]. Gastric cancer can be further classified according to the disease site, which includes gastric cardia cancer, gastric cancer, and gastric antrum cancer [2]. Recent epidemiological data have indicated that there are about 951,000 new cases of gastric cancer around the world and about 723,000 deaths due to gastric cancer, thereby ranking gastric cancer as the fifth most common and third most malignant tumor with the highest mortality rate [3].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, tumor recurrence has been reported in half of the patients who undergo surgery [11]. In addition, chemotherapy, which induces tumor cell cytotoxicity and eventually death [12], has not significantly improved the overall survival of patients with gastric cancer because of poor selectivity and toxicity [2,10,13,14]. Thus, the traditional treatment schemes for gastric cancer do not meet clinical needs, and the development of novel treatment methods is imperative [15].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolism in tumours plays a key role in cellular logistics for rapid proliferation, maintenance of redox homeostasis and in epigenetics and reprogramming [28]. In recent years, there have been many metabolomic studies on GC and reported various metabolites related to GC [2931]. As a result, the perturbed pathways resulting from the metabolomic analysis of GC were similar, consistently showing a metabolism disorder of amino acids, lipids, and glycolysis in Figure 8.…”
Section: Discussionmentioning
confidence: 98%
“…Generally, undifferentiated cancer consists of poorly differentiated cancer and signet ring cell cancer. Many studies have reported that early SRC type tended to be confined to the mucosal layer and had a lower LNM rate and a higher 5-year survival rate than the non-SRC type [21][22][23]. On the contrary, the Poorly-D type is more likely to invade the submucosal layer, which may contribute to LNM.…”
Section: Discussionmentioning
confidence: 99%